Modelling of drying kinetics of single apricot - Togrul, IT; Pehlivan, D (Elsevier Sci Ltd, 2003)
In this work, the drying behaviour of single apricots, hanging in the flow direction of hot air in a drying chamber, was investigated. In the experiments, the air was passed through the chamber at a variety of flow rates (0.2, 0.5, 1.0 and 1.5 m/s) and temperatures (50, 60, 70 and 80 degreesC). In order to obtain drying data, the changes in the mass and inner temperatures of the apricots were recorded as well as the drying air properties. The variations of drying rates with time and moisture content were used to test fourteen different one-layer drying models given in the literature and a new model was developed. Among all the models, the logarithmic model was found the best for explaining the drying behaviour of apricots. The effects of drying air flow rates and temperatures on the constants and coefficients of the models were also studied by multiple regression analysis. It was found that the new model could represent single apricot drying kinetics within 99.9% accuracy. The moisture transfer from the apricots occurring during the falling-rate period of drying was characterised by determining experimentally the apparent diffusion coefficient into the air. It was found, by multiple regression analysis, that the diffusion coefficients could be expressed within 97.3% accuracy, depending on the air flow rates and inside temperatures of the single apricot. In studying the consistency of all the models, some statistical tests, such as reduced chi(2), mean bias error and root mean square error were also used as well as correlation coefficients. The results of these tests have also confirmed the consistency of the logarithmic model. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: apricot; drying; mathematical model; moisture diffusion; statistical test